2018
DOI: 10.18196/agr.4265
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pola Pemilikan Lahan Terhadap Produksi, Alokasi Tenaga Kerja, dan Efisiensi Usahatani Padi

Abstract: Land is the main input in agricultural production and also a wealthgenerating asset for farmers. There are three common forms of agricultural land ownership:owned land, rented land, and sharecropped (kedokan) land, where each of them are directly affects the farming performance. The purpose of this study was to analyze the effect of land ownerships on farm production, labor use, and farm economic efficiency. The sample used in this study were 150 farmers equally distributed in each ownership group from a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Farm owners have a higher incentive to invest in adaptation practices [89]. A study in Pakistan and Indonesia found that insecure land tenure decreases adaptation practices [90] and makes farmers less cautious in terms of their farming, manifesting, for example, through an absence of soil conservation [91]. The positive effect of secure land tenure on adaptation practices, however, has potential disadvantages when the adaptation yielded unintended maladaptive outcomes.…”
Section: Economics Factorsmentioning
confidence: 99%
“…Farm owners have a higher incentive to invest in adaptation practices [89]. A study in Pakistan and Indonesia found that insecure land tenure decreases adaptation practices [90] and makes farmers less cautious in terms of their farming, manifesting, for example, through an absence of soil conservation [91]. The positive effect of secure land tenure on adaptation practices, however, has potential disadvantages when the adaptation yielded unintended maladaptive outcomes.…”
Section: Economics Factorsmentioning
confidence: 99%
“…Land tenure security also plays a crucial role in Indonesian agriculture. Land tenure security increases the productivity and profitability of rice farming in Indonesia [41], the probability of participating in contract farming [34], and the adoption of certified seed plants [37]. A weak land tenure security lessens farm investment and makes the farmer more vulnerable to shocks, including climate change.…”
Section: Land Tenurementioning
confidence: 99%
“…A research in Jember Regency has reported that agricultural land is the most important asset for farmers so that wider land ownership can have a positive impact on the increase in profits derived from farming activities undertaken (Rondhi and Adi, 2018). However, the agricultural land managed by farmers is increasingly widespread and as a consequence, this increases the risk of farmers in carrying out farming activities on the peri-urban areas, both the risk of crop failure due to pests and plant diseases, or due to environmental conditions that are not suitable for growing plants and the risk of selling prices of agricultural products come down during the harvest (Purbiyanti et al, 2017;Prasada et al, 2018).…”
Section: Factors Affecting Farmers' Perceptions Of the Agricultural Lmentioning
confidence: 99%